Pengaruh Media Sosial dan Strategi Pemasaran Digital terhadap Peningkatan Penjualan pada Usaha Mikro, Kecil, dan Menengah (UMKM) di Surabaya Selatan - Zainal Aprianto Bagus Pratama; Iswati Iswati; Anis Fitriyasari (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2024)
This research is to find out more about "The Influence of Social Media and Digital Marketing Strategy on Increasing Sales in Micro, Small and Medium Enterprises (MSMEs) in South Surabaya" in accordance with the problems raised, namely the relationship between social media and digital marketing strategies on increasing sales in MSMEs in South Surabaya. The background to this research is due to the development of digital marketing in the business world, so it is important for MSMEs to follow existing developments. The aim of this research is to find out whether there is an influence of social media and digital marketing strategies on increasing MSME sales. The method used is a quantitative method by distributing a questionnaire in the form of a Google Form to MSMEs in South Surabaya. The researcher used purposive sampling, so the researcher chose a sample that matched the characteristics of the respondents from the population obtained. After that, the collected data was processed using the SPSS program and calculated using Multiple Linear Regression. The conclusion of this research is that there is a relationship between social media and digital marketing strategies in increasing MSME sales.